Space as Metaphor for Resistance in Alice Munro’s "The Office" - Sharma, Chaandani (NPRC Journal of Multidisciplinary Research, 2025)
Background: Alice Munro's short story "The Office" describes a female writer's struggle for independent creative agency in a patriarchal environment. The story echoes the major feminist claims, such as Virginia Woolf's statement that women should have financial independence and a literal and figurative room of their own, and the ideas of Simone de Beauvoir that work is what liberates women from parasitic dependence.Objective: The objective of this paper is to examine the protagonist's yearning for independence and her fight against patriarchal oppression. An attempt is made to understand what form and mode of resistance she puts up and whether it is successful or not in the end.Methods: This analysis is qualitative, with a literary-critical approach that reads Munro's story through the theoretical lenses of Woolf's A Room of One's Own and Beauvoir's The Second Sex. Close textual analysis of the primary source is supported by secondary criticism from Munro scholars.Analysis: This paper identifies that the protagonist rents an office as a main act of resistance and is symbolic of claiming intellectual and physical space. These strategies of hers are subtle and non-confrontational in nature; she seeks permission from her husband and internalizes societal ridicule. This resistance is systematically thwarted by the invasive acts of her landlord, Mr. Malley, and the deep-rooted gender dynamics within her household, leading to her eventual capitulation.Conclusion: The paper consequently concludes that, though the protagonist does long for freedom and is even able to succeed in certain concrete actions of resistance, the subtlety of her strategies along with strong patriarchal pressures prevents her from gaining durable autonomy. Munro thereby criticizes the continuous social obstacles that stand in the way of fulfilling women's creative and professional ambitions.Novelty: While Munro's feminism is widely acknowledged, this study provides a focused analysis of the specific nature and strategies of resistance in "The Office," tracing its nuanced failure and contributing to a deeper understanding of how patriarchal domination operates in the mundane, professional spheres of women's lives.